Ostrowski Via a Two Functions Pompeiu's Inequality - Dragomir Silvestru Sever (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2016)
In this paper, some generalizations of Pompeiu's inequality for two complex-valued absolutely continuous functions are provided. They are applied to obtain some new Ostrowski type results. Reverses for the integral Cauchy-Bunyakovsky-Schwarz inequality are provided as well.